Connect. Convene. Facilitate. Scale: Locating the role of the CGIAR Research Initiative on Diversification in East and Southern Africa (Ukama Ustawi) Scaling Hub within the East and Southern Africa Agribusiness Support Landscape - Inoubli, Aziza; Adebola, Mariam; Saunders, David; With, Lisa (International Livestock Research Institute, 2022)
Agriculture is the largest sector in East and Southern Africa, employing 65% of the population and contributing over 30% of the region’s GDP . Despite its vital role in the region’s economy and global food production, the sector faces many challenges, including climate change, poor infrastructure, and global supply chain disruptions, leading to high levels of food insecurity and poverty in the region. Introducing climate-resilient solutions to enable climate adaptation, strengthen value chains, and empower smallholder farmers with a focus on youth and women are key to strengthening the sector and driving its growth.